Pelatihan Penulisan Karya Ilmiah sebagai Wahana Pemecah Masalah dan Solusi Praktis untuk Meningkatkan Prestasi Akademis - Budiyono, Sri; Ngumarno, Ngumarno; Nugroho, Aji Wisnu; Pranawa, Erry; Susena, Danang; Santoso, Gunawan Budi; Suranto, Much; Rahmah, Tariza Aulia (Journal of Dedicators Community, 2024)
The purpose of this service is to provide learning in the context of fostering a good Indonesian language and at the same time directing learners to write scientific articles. The simplest activity is carried out by counseling participants, especially using it in official activities, writing scientific articles. The method used in this service is to give lectures, interactive dialogues, structural assignments, and presentations for participants whose work will be tested in a scientific work competition. The results of the learning provided by the resource persons, with friendly faces and attitudes full of jokes, laughter, stories, and so on, brought the impact of the counseling atmosphere that seemed more intimate and close. The resource persons tried to put aside the formal impression so that there was no longer a tense atmosphere. There are discussion forums, jokes, and stories. Family matters in counseling make it easier for learners to know good and correct language, and understand indicators or requirements in writing articles that have characteristics: systematic, empirical, logical, reductive, replicable, and transmissible.